Silica Gel‐mediated Synthesis of β‐Enamino Esters and its Application for the Synthesis of Indeno 4‐Hydroxypyridin‐2(1H)‐Ones. (30th January 2019) - Kim, Soong‐Hyun; Bae, Seri; Ko, Eun Bi; Park, Ga Young; Lee, Eunhye; Hwang, Hee Jong; Im, Chun Young; Song, Minsoo
Abstract : The full scope of SiO2 ‐based condensation of aliphatic or aromatic amines and β‐keto esters to give β‐enamino esters was examined. Functionalized linear β‐enamino esters were easily obtained from SiO2 ‐based condensation of β‐keto esters and amines only after simple filtration. It was also demonstrated that cyclic β‐enamino esters with 99% purity can be prepared in a practically large scale (60 g) without using silica gel column chromatography. The utility of the present method was fortified by the preparation of pharmaceutically useful indeno‐4‐hydroxypyridin‐2(1H)‐one analogue11 . Abstract :